PENGARUH PERTUMBUHAN TANAMAN BAWANG MERAH (Allium ascalonicum L. ) SEBAGAI AGEN FITOREMEDIASI DENGAN PENYERAPAN LOGAM BESI Fe PADA MEDIA TANAM LUMPUR LAPINDO - Masda Alni; Ir. Saiful Arifin.MM (GEMA, 2022)
The Lapindo mudflow that occurred in 2006 was one of the eruptions that contained a lot of gas and metal. One of them is Fe metal, a metal component that pollutes the climate in high quantities can contaminate plants, so that the polluted climate cannot be utilized, thus so that the Lapindo mud can be utilized, phytoremediation is needed, which means efforts to recover polluted media, with this plant Shallots (Allium ascalonicum L.) is one of the plants that can absorb metals because it is seen from the synthetic that 80% of the substance is water. In this study, it was carried out on the land of Jetis Village, Sidoarjo District, starting from December 2021 to February 2022 with a descriptive method and using a mixture of Lapindo mud as a planting medium, which consisted of 4 types of treatment, namely LP0 Control, LP1 10% Lapindo Mud, LP2 20 % Lapindo mud, LP3 30% Lapindo mud. The data was tested using regression analysis, with the results of the analyzed data showing that 0% treatment (control) had better growth than the addition of Lapindo mud concentration (10% -30%) in this case experiencing inhibition of onion plant growth. (Allium ascalonicum L.).